2017
DOI: 10.1182/blood-2017-02-767384
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β–induced intracellular PAI-1 is responsible for retaining hematopoietic stem cells in the niche

Abstract: Key Points• TGF-b-induced intracellular PAI-1 regulates the balance of HSPCs localization between BM and periphery.• Intracellular PAI-1 inhibits Furin-dependent maturation of MT1-MMP in HSPCs, resulting in the suppression of HSPC motility.Hematopoietic stem and progenitor cells (HSPCs) reside in the supportive stromal niche in bone marrow (BM); when needed, however, they are rapidly mobilized into the circulation, suggesting that HSPCs are intrinsically highly motile but usually stay in the niche. We question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 59 publications
1
36
0
Order By: Relevance
“…Recently, we showed that TGF-β signaling regulates the motility of HSPCs in the niche through selective upregulation of iPAI-1 expression in HSPCs 17,20 . Therefore, we hypothesized that the TGF-β−iPAI-1 axis is similarly operational in CML-LSCs.…”
Section: Tgf-β-ipai-1 Axis Is Activated In Cml-lscsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, we showed that TGF-β signaling regulates the motility of HSPCs in the niche through selective upregulation of iPAI-1 expression in HSPCs 17,20 . Therefore, we hypothesized that the TGF-β−iPAI-1 axis is similarly operational in CML-LSCs.…”
Section: Tgf-β-ipai-1 Axis Is Activated In Cml-lscsmentioning
confidence: 99%
“…Like their normal hematopoietic counterparts, CML-LSCs are presumed to reside in specific niches in the BM microenvironment, which likely to contribute to relapse after chemotherapy [14][15][16] . Recently, we have uncovered a pathway by which TGF-β signaling regulates HSPC retention in the niche 17 . TGF-β induces the expression of plasminogen activator inhibitor-1 (PAI-1), a major physiologic serine protease 4 inhibitor (SERPIN) of the fibrinolytic system.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, $20% of BM LT-HSCs that are physically connected to megakaryocytes are quiescent, as assessed by their cell cycle status (G0) and intracellular ROS concentration [8,45] (Figure 2C). TGFb from megakaryocytes promotes HSPC retention in the niche, at least partly by repressing expression of MMP14, which is downstream of Smad3 and PAI-1 in the TGFbR signaling pathway; and, inhibition of TGFb signaling with the small-molecule inhibitor LY364947 activates MMP14 and the subsequent disruption of adhesion molecules can promote LT-HSC mobility [46]. Megakaryocytes express TIMPs as well as MMP2 and MMP9, which could provide a means of local TGFb regulation, and HSPCs express MMP2, 9, and 14.…”
Section: Tgfbmentioning
confidence: 99%